2014
DOI: 10.1007/s10875-014-9997-3
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Granulomatous Disease in Morocco: Genetic, Immunological, and Clinical Features of 12 Patients from 10 Kindreds

Abstract: The clinical features and infectious agents found in these patients were similar to those in CGD patients from elsewhere. The results of mutation analysis differed between kindreds, revealing a high level of genetic and allelic heterogeneity among Moroccan CGD patients. The small number of patients in our cohort probably reflects a lack of awareness of physicians. Further studies on a large cohort are required to determine the incidence and prevalence of the disease, and to improve the description of the genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…Many variants in the NCF2 gene leading to CGD with a range in severity have been identified (Table 2) (AlKhater, 2019; Baba et al, 2014; Badalzadeh et al, 2012; Bakri et al, 2009; Ben‐Farhat et al, 2016; Chou et al, 2015; El Kares et al, 2006; Gentsch et al, 2010; Kannengiesser et al, 2008; Koker et al, 2009, 2013; Martel et al, 2012; Raptaki et al, 2013; Roesler et al, 2012; Roos et al, 2014; Teimourian, de Boer, & Roos, 2010; Vignesh et al, 2017; Wu, Wang, Zhang, & Chen, 2017). Part of this variability is due to the residual activity of the p67 phox protein as observed in patients with an Ala202Val substitution (Koker et al, 2013; Roos et al, 2014) or in patients with a splice variant that deletes exons 11 and 12 (Roesler et al, 2012), all of which have a less severe form of CGD with a delayed onset compared with p67 phox null mutations (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Many variants in the NCF2 gene leading to CGD with a range in severity have been identified (Table 2) (AlKhater, 2019; Baba et al, 2014; Badalzadeh et al, 2012; Bakri et al, 2009; Ben‐Farhat et al, 2016; Chou et al, 2015; El Kares et al, 2006; Gentsch et al, 2010; Kannengiesser et al, 2008; Koker et al, 2009, 2013; Martel et al, 2012; Raptaki et al, 2013; Roesler et al, 2012; Roos et al, 2014; Teimourian, de Boer, & Roos, 2010; Vignesh et al, 2017; Wu, Wang, Zhang, & Chen, 2017). Part of this variability is due to the residual activity of the p67 phox protein as observed in patients with an Ala202Val substitution (Koker et al, 2013; Roos et al, 2014) or in patients with a splice variant that deletes exons 11 and 12 (Roesler et al, 2012), all of which have a less severe form of CGD with a delayed onset compared with p67 phox null mutations (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, before BCG vaccination at birth was proscribed in France, 22% of French patients with CGD had a reaction to BCG. 29,45 In a Moroccan series, 2 (16.7%) of 12 vaccinated patients presented with clinical BCG disease, 19 and in a Mexican series, 16 (32%) of 50 patients with CGD vaccinated with BCG presented with clinical BCG disease (Blancas Galicia, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…11 In a review of the literature, Deffert et al 12 reported a total of 297 cases of mycobacterial infections in patients with CGD. [13][14][15][16][17][18][19][20][21][22][23][24] BCG disease has been reported in 220 (74%) patients with CGD. 11 Similarly, tuberculosis has been reported in 59 (20%) patients.…”
mentioning
confidence: 99%
“…Many studies in the northern region of Africa describe an autosomal recessive transmission mode for PIDs and some have reported novel autosomal recessive gene mutations. [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] Due to this fact, the northern region of Africa seems to be a distinctive epidemiological area for the study of genetic diseases, such as PIDs, which has drawn the attention of many researchers in the past decade. Table 5 illustrates some of the studies describing molecular characterisation, novel genetic mutations and founder effects of PIDs undertaken mainly in Africa.…”
Section: Novel Mutations In the African Populationmentioning
confidence: 99%
“…Compound heterozygous variant in LRBA (NM_006726) (c 3296 C>G and c.3407 C>T). Owen [41] (2015) SA 7 SA families Complement deficiency Complement C5 gene mutation c.754G>A:p.A252T; common in the Western Cape Jlajla [42] (2014) Tunisia 1 Tunisian family C1q deficiency Novel g.5580G4C mutation Sassi et al [43] Ben-Mustapha [44] (2014) Tunisia 6 Tunisian patients MSMD Founder effect for the c.298_305del mutation in the IL12B gene Baba [45] (2014) Morocco 12 CGD Four different mutations of CYBB, a recurrent mutation of NCF1 and a new mutation of NCF2 in three patients Ben-Mustapha et al [46] (2013) Tunisia 34 (belonging to 28 Tunisian families)…”
Section: Treatmentsmentioning
confidence: 99%